2006
DOI: 10.1089/jwh.2006.15.98
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence among Female Flight Attendants: A Meta-Analysis of Published Data

Abstract: Background: Flight attendants are exposed to cosmic ionizing radiation and other potential cancer risk factors, but only recently have epidemiological studies been performed to assess the risk of cancer among these workers. The aim of the present work was to evaluate the incidence of various types of cancer among female cabin attendants by combining cancer incidence estimates reported in published studies.Methods: All follow-up studies reporting standardized incidence ratio (SIR) for cancer among female flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 41 publications
3
45
1
3
Order By: Relevance
“…These findings were confirmed in a recent meta-analysis that included both military and civilian pilots (25). Among female flight attendants, seven studies found elevated risks of breast cancer, and six studies reported a higher than expected malignant melanoma risk (20,26). Airline personnel, however, differ from other shift workers both with respect to their occupational exposures to cosmic radiation (21) and their greater opportunity for recreational solar exposure.…”
Section: Schwartzbaum Et Almentioning
confidence: 65%
See 2 more Smart Citations
“…These findings were confirmed in a recent meta-analysis that included both military and civilian pilots (25). Among female flight attendants, seven studies found elevated risks of breast cancer, and six studies reported a higher than expected malignant melanoma risk (20,26). Airline personnel, however, differ from other shift workers both with respect to their occupational exposures to cosmic radiation (21) and their greater opportunity for recreational solar exposure.…”
Section: Schwartzbaum Et Almentioning
confidence: 65%
“…Airline personnel, however, differ from other shift workers both with respect to their occupational exposures to cosmic radiation (21) and their greater opportunity for recreational solar exposure. It is therefore difficult to know which factors are responsible for the observed excess cancer risks in this group of workers (20).…”
Section: Schwartzbaum Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Studies suggest that flight attendants have an increased incidence of breast cancer compared to the general population (1,2). However, the reason is unclear.…”
mentioning
confidence: 99%
“…An example was that conducted by Buja et al [24]. Bayesian hierarchal models were applied to the results of 7 published studies after standardized incidence ratios (SIRs) were estimated.…”
Section: Breast Cancermentioning
confidence: 99%